1981
DOI: 10.1104/pp.68.4.950
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Linoleic Acid by Barley Lipoxygenase and Hydroperoxide Isomerase

Abstract: The oxidation of linoleic acid in incubation mixtures containing extracts of barley lipoxygenase and hydroperoxide isomerase, and the production of these enzymes in quiescent and germinated barley, were investigated.The ratio of 9-hydroperoxylinoleic acid to 13-hydroperoxylinoleic acid was higher for incubation mixtures contain extracts of quiescent barley than for mixtures containing extracts of germinated barley, production of 13-hydroperoxylinoleic acid from germinated barley exceeded that of quiescent barl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 20 publications
1
5
0
1
Order By: Relevance
“…an ␣-ketol, and (ii) by reproducing adduction by exposing LTP1 to either linoleic acid and an aqueous suspension of isolated defatted barley embryo or 9-HPOD and maize AOS. 9-LOX and AOS are specifically located in the embryo (40,41), in agreement with the fact that LTP1 adduction requires the presence of the embryo.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…an ␣-ketol, and (ii) by reproducing adduction by exposing LTP1 to either linoleic acid and an aqueous suspension of isolated defatted barley embryo or 9-HPOD and maize AOS. 9-LOX and AOS are specifically located in the embryo (40,41), in agreement with the fact that LTP1 adduction requires the presence of the embryo.…”
Section: Discussionsupporting
confidence: 49%
“…It should be noted that 9-LOX is the major LOX in the embryo of quiescent barley seeds (42,43) and that AOS is the major enzyme metabolizing lipoxygenase-generated hydroperoxides in embryos of quiescent barley grains (41). The very efficient trapping of 9,10-allene oxide by 50 M LTP1 in an aqueous environment (about 55 M water) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gardner (1970) reported that lipoxygenase was localized primarily in the seed germ tissue of mature hybrid corn. Lipoxygenase activity was found primarily in the germ tissue of cereal seeds such as wheat (Auerman et al, 1971;Von Ceumern and Hartfiel, 1984), barley (Lulai and Baker, 1976;Lulai et al, 1981), and rice (Yamamoto et al, 1980); however, the subcellular location of lipoxygenase in germ tissue has not been reported (Gardner, 1988).…”
Section: Ph Optimum For Activity and Ph Stabilitymentioning
confidence: 99%
“…We think that this inconsistency is due to the presence of other competing pathways to the transformation of 2( E )-nonenal. Competing enzymes for 9-HPL-like activity would be hydroperoxide isomerase, 12,13) peroxygenase-like activity, 8,15) or allene oxide synthase. 19) In soybean seeds, it is reported that HPL cleaves 9-HPOD to form 3(Z )-nonenal, and then 3(Z )-nonenal is sequentially converted into 4-hydroperoxy-2( E )-nonenal and 4-hydroxy-2( E )-nonenal by the action of soybean LOX-1 and peroxygenase, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It was only characterized as an enzyme that converts 13-HPOD into a-ketol [9-hydroxy-10-oxo-(12Z )-octadecenoic acid] and gketol [13-hydroxy 10-oxo-(11 E )-octadecenoic acid], so that the possibility that it might also contain HPL has not been veriˆed. 12,13) Schwarz and Pyler reported that hydroperoxide-decomposing activity is also detected in malt, but only if it is extracted with a buŠer containing Triton X-100, suggesting the enzyme is tightly bound to the insoluble barley grist. 14) Because this activity was not detectable in the soluble fraction of mash at any time during mashing, they concluded this activity is not involved in the lipid oxidation.…”
mentioning
confidence: 99%